The Role of Drama in Accomplishing the Art of Communication: Exploring the Interconnection between Drama and Communication (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article tries to showcase the conspicuous role of drama as a performing art to develop the art of transmition, that is, communication skill. The paper also demonstrate how drama and communication are consolidated each other from the ancient time as displayed by Bharat Muni in his treatise called 'Natya Shastra'. This article will spread the splashes of light over the importance of participation by students and Emphasis how it can, in turn, cultivate the overall intellectual as well as psychological growth.